2007
DOI: 10.1590/s0034-89102006005000048
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of salivary cotinine level: a population-based study in Brazil

Abstract: Determinantes dos níveis de cotinina salivar: um estudo de base populacional no Brasil ABSTRACT OBJECTIVE: A cross-sectional population-based study was conducted to assess, in active smokers, the relationship of number of cigarettes smoked and other characteristics to salivary cotinine concentrations. METHODS:A random sample of active smokers aged 15 years or older was selected using a stepwise cluster sample strategy, in the year 2000 in Rio de Janeiro, Brazil. The study included 401 subjects. Salivary cotini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
5
20
1
Order By: Relevance
“…Then, the association between smoking categories and cotinine levels was assessed by using a generalized linear model (GLM) with gamma distribution, adjusting for age, sex, BMI, and country (because nicotine contents may differ among brands of cigarettes). It has been reported that age, sex, and BMI modify the relationship of number of cigarettes to cotinine (15,16). BMI was considered as a confounder because subjects with a higher BMI tend to exhibit lower cotinine concentrations, possibly because of the distribution of cotinine into a bigger volume of blood (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the association between smoking categories and cotinine levels was assessed by using a generalized linear model (GLM) with gamma distribution, adjusting for age, sex, BMI, and country (because nicotine contents may differ among brands of cigarettes). It has been reported that age, sex, and BMI modify the relationship of number of cigarettes to cotinine (15,16). BMI was considered as a confounder because subjects with a higher BMI tend to exhibit lower cotinine concentrations, possibly because of the distribution of cotinine into a bigger volume of blood (16).…”
Section: Discussionmentioning
confidence: 99%
“…This biomarker has been linked to several modulating factors, including gender, body mass index (BMI), race, number of cigarettes, types of cigarette, filter, and the way the product is smoked (15,16). Picket and colleagues (17) have compared serum cotinine levels in nonsmokers living under extensive, limited, and no coverage smoke-free laws in different locations in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Smokers who consume cigarettes immediately after waking have higher blood cotinine levels than smokers who refrain from smoking a half hour or more after waking (2)(3)(4)(5)(6). The levels of cotinine are about twice as high in smokers who smoke within 5 minutes after waking than in smokers who waited for an hour or more after adjusting for the number of cigarettes smoked per day (CPD).…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of dependence may be related to a higher consumption of nicotine and, consequently, higher levels of cotinine 25 .…”
Section: Discussionmentioning
confidence: 99%